2022
DOI: 10.3390/ijerph191912936
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the “Triple-Layer Medical Security” Policy on the Vulnerability as Expected Poverty of Rural Households: Evidence from Yunnan Province, China

Abstract: China launched the “critical battle against poverty” nationwide in 2012. As its main battlefield, Yunnan province promulgated the “triple medical security” (TMS) policy in 2017. This study, based on the pooled cross-section database of 2015–2020 of registered poor households in Yunnan province, employed the logit model to examine the effect of TMS on the vulnerability as expected poverty (VEP) of these households. It found that increasing the reimbursement rates for overall medical expenses and inpatient expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…First, this study should have considered differences in the prevalence of chronic and acute diseases. Some studies have revealed that HPAP may have different effects on VEP in patients with chronic or severe diseases [ 21 ]. Second, the limited duration of cross-sectional data used in this study may have negatively affected our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study should have considered differences in the prevalence of chronic and acute diseases. Some studies have revealed that HPAP may have different effects on VEP in patients with chronic or severe diseases [ 21 ]. Second, the limited duration of cross-sectional data used in this study may have negatively affected our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional measurements and definitions related to poverty provide a static analysis of the level of welfare of a household or individual at a point in time [ 25 ]. These conventional approaches do not predict future poverty status and are ex-post indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poverty vulnerability is usually defined by some relative benchmarks, such as Vulnerability as Expected Poverty (VEP) [48], Vulnerability as Low Expected Utility (VEU) [49] and Vulnerability as Uninsured Exposure to Risk (VER) [50]. Compared with VEU and VER, VEP has advantages in practical applications [51]. First, its data requirements are relatively low.…”
Section: Evaluation Indicatormentioning
confidence: 99%